ANALISIS KOMPETENSI YANG DIBUTUHKAN NELAYAN DALAM MENGHADAPI PERKEMBANGAN TEKNOLOGI KAPAL PROPULSI LISTRIK - Nurpalah, Muhamad Rizki; Hamid Abdillah; Iskendar (Politeknik Negeri Cilacap, 2024)
Research on the competencies needed by fishermen in an era of increasingly rapid technological progress aims to explain the basic competencies that electric propulsion boat users need to have. Analysis based on implementation needs to be carried out with the aim of adapting the use of water transportation technology, namely ships with electric power, according to the required competencies. This research was carried out using a descriptive qualitative approach method with a literature study type of research. The research was carried out by collecting data from secondary sources such as books and journal articles related to the variables and subjects of this research. From the research results, a comparison was obtained between the abilities currently possessed by fishermen, and the abilities that fishermen must have in the future in facing developments in water transportation. It is known that, in terms of use, users need to understand the use of electric propulsion ships and K3 in their application, in terms of understanding more about the main components of the technology used, in terms of maintenance being able to repair and maintain the components, and understanding the social impacts that occur as well as the advantages and disadvantages of using them. Therefore, efforts are needed to educate the public so that they can easily receive clear information about electric propulsion ship technology, so that the results of the development of this technology can be accepted by the general public.